1999
DOI: 10.1109/8.774152
|View full text |Cite
|
Sign up to set email alerts
|

Phase-only shaped beam synthesis via technique of approximated beam addition

Abstract: A new method for phase-only phased-array beampattern synthesis is derived. The method is appropriate for the synthesis of coverage patterns for satellite communications, where a minimax goal of maximizing the worst-case beamforming gain to a set of service locations is desired. The new approach, called the technique of approximated beam addition, is found to be computationally attractive relative to conventional methods, yet offers optimal performance. Included are a theoretical consideration of optimality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…equal gain combining). Most literature considers a single weight vector (with variable phases only) that should be designed to match certain performance criteria, e.g., [6], [15], and [16]. The paper [10] considers an APN with multiple outputs, and it is shown that any desired weight vector can always be obtained by linearly combining two phase-only beamformers, thus is sufficient.…”
Section: A Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…equal gain combining). Most literature considers a single weight vector (with variable phases only) that should be designed to match certain performance criteria, e.g., [6], [15], and [16]. The paper [10] considers an APN with multiple outputs, and it is shown that any desired weight vector can always be obtained by linearly combining two phase-only beamformers, thus is sufficient.…”
Section: A Connectionsmentioning
confidence: 99%
“…After selecting and , we compute the residual vector and proceed similarly as (15), where After selecting and , we could continue the process with the residual vector However, and are not orthogonal, and better coefficients and can be computed at this point, leading to a smaller residual. This requires to solve (16) (17) where is a orthonormal matrix and a 2 2 upper triangular matrix. The solution to (16) is and the corresponding (smaller) residual is which is the projection onto the orthogonal complement of the column span of .…”
Section: B Quantized Matching Pursuitmentioning
confidence: 99%
“…The trivial solution would be amplitude tapering, or, as an extreme case, the use of only a part of the transmit antenna; but this causes a significant loss of radiated power; furthermore, it may lower the overall efficiency since the high-power amplifiers in the T/R modules are no longer driven in saturation. Another solution is phase tapering, but the derivation of appropriate phase coefficients is a complex task that requires, in general, complicated numerical optimization techniques [42], [43].…”
Section: A Limitations Of a Fixed-aperture Illuminationmentioning
confidence: 99%
“…Tunable RF beamformer architectures with reduced number of RF chains have been previously proposed for low-power receivers fully implemented in Silicon [11,12,25]. However, the power levels of such designs are much lower than the power levels required in cellular base-stations, which can easily exceed 47 dBm.…”
Section: Existing Rf Beamforming Networkmentioning
confidence: 99%